The Longer-Term Effects of Management-Led Buy-Outs - Mike Wright; Nick Wilson; Ken Robbie (Journal of Entrepreneurial and Small Business Finance, 1996)
There is now extensive evidence on short-term performance improvements in buy-outs, but little relating to the longer-term. This paper examines the relatively neglected area of the longevity and longer-term effects of smaller buy-outs. In terms of longevity, the evidence presented shows that the majority remain as independent buy-outs for at least eight years after the transaction, and that entrepreneurial actions concerning both restructuring and product innovation are important parts of entrepreneurs' strategies over a ten year period or more. For the first time, the paper also provides an analysis of the financial performance and productivity of a large sample of buy-outs and non-buyouts. It shows that on a variety of financial ratios buy-outs significantly outperform a matched sample of non-buy-outs, especially from year 3 onwards. Analysis of post buyout efficiency of survivor buy-outs, using regression analysis to estimate augmented Cobb-Douglas production functions, shows that buy-outs are superior to matched nonbuy-outs with a productivity differential of the order of 9% on average from year t+2 onwards. The evidence of superior longer term performance suggests that venture capitalists may need to consider their investment perspectives carefully, particularly in respect of exit versus second round investment. For financiers it is clear that the buy-out concept can be successfully applied to growth as well as restructuring cases.
Keywords: G32; G34; M13; 650; Management-Led Buy-Outs; MBO; LBO